Evaluación de productividad de flores tropicales bajo dosel de bosque nativo en Misiones - Haussecker, Ricardo Daniel (2019)
With the aim of generating a low cost commercial business, the productivity of 15 genotypes of tropical plants for cut flowers was evaluated. They have been planted in a 2 x 3m pattern under an 18 m high degraded forest with up to 1 m undergrowth. Plants life has been affected by winter frost: 100% for Heliconia pseudoamygdyana, Musa coccinea and M. ornata; 0% for H. ´Jacquinii´, H. stricta ´Firebird´, H. ´Golden torch´. The number of flowered branches per plant and year has been: Costus barbatus, 5,4; Heliconia pseudoamygdyana, 3,1; Musa coccinea, 2,7 and H. manthiasiae, 2.